Political power and women's representation in Latin America - Schwindt-Bayer, Leslie A. (New York ; Oxford : Oxford University Press, 2010)
The number of women elected to national legislatures has grown significantly over the past 30 years. Using a comparative study of recent trends in women's representation in Latin America this book develops an integrated theory of women's representation that analyzes trends in relation to various facets of political representation.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Women legislators -- Latin America; Women -- Political activity -- Latin America